Proceedings from the grand inauguration of the project Consortium for Scaling-Up Climate-Smart Agriculture in South Asia (C-SUCSeS) - Pal, Barun Deb; Kabir, Razin; Pradhan, Mamata; Gyeltshen, Kinzang (International Food Policy Research Institute, 2022)
Driven by the need to produce more food for an ever-increasing population that is further marred with declining and degrading natural resource base, adapting to and mitigating climate change have posed a big challenge. It is an established fact that in agriculture, fertilizers, flooded rice cultivation, energy use in irrigation, tillage, and enteric emissions from ruminant animals are the main contributors of greenhouse gases, which accounts to about one-fourth of the total emissions. The evolution of climate-smart agriculture (CSA) emerged as a scientific response to this multi-headed hydra, which helps achieve higher production with reduced emission. The fact remains that the small farm holders of South Asia, who are already facing several non-climatic stresses, have limited capacity to adopt new technologies. There are a host of barriers in the form of limited access to natural resources, information, finance, and above all, low human capital that limit the adoption of technology. The global community is aware of these climate change challenges and has initiated programs to overcome these challenges across the world. In this context, and to meet the Sustainable Development Goals (SDGs) related to climate change mitigation and adaptation, there is a need for evidence-based research that have the potential to bring about transformative change in agriculture and food systems.